METHODS OF DATA CLASTERIZATION IN DIGITAL PROCESSING OF SPEECH SIGNALS - Tkachenko, Alexander; Feferman, Oleg (Scientific Works of Vinnytsia National Technical University, 2015)
The paper considers the main methods of data clusterization, their advantages and disadvantages are analyzed, further research lines are formulated.